Development of teaching material based on plomp development model to support indonesian merdeka curriculum on chemical bonding topic in Phase E - Aviva Alamanda; Mawardi Mawardi; Okta Suryani (Jurnal Pijar Mipa, 2023)
This research aims to develop teaching materials that support independent curriculum learning by measuring the adequacy and practicality of the Phase E chemical bonding topic. The type of research is Educational Design Research (EDR) using the Plomp development model. This study was conducted in the 2022/2023 academic year at senior high school SMAN 8 Padang, Indonesia. Data were collected using efficacy and utility questionnaires. As a result, we found that the valid categories have an average relevance of 0.85 in developing teaching materials. Utility test results for student answers show an average of 93% practicality in the very practical category, and utility test results for teacher answers show an average of 97% practicality in the very practical category. Overall, the results demonstrate that developing teaching materials that support independent curriculum learning using Phase E chemically bonded materials is valid and practical. Chemical bonds are a vital material taught in Phase E. The chemical bonds described in this article include ionic and covalent bonds. This textbook provides definitions of ionic and covalent bonds, examples of assignments, and discussions. In addition, primary chemistry education is explained with examples of how chemical bonds are applied in everyday life to make it easier to understand chemically bonded substances. The material includes practice assessment questions to check how well students understand the material. This material is expected to be useful for teaching and learning activities for teachers, and it will be easy for students to learn and understand.